ANALYSIS OF WHATSAPP SOCIAL MEDIA USE IN THE DISTANCE LEARNING PROCESS AT ISLAMIC ELEMENTARY SCHOOL - Sri Enggar Kencana Dewi; Jami Ahmad Badawi; Deni Indrawan; Muh Miftahurrazikin; Diah Rizki Nur Khalifah (JIP Jurnal Ilmiah PGMI, 2022)
The distance learning policy requires the provision of materials and assignments through social media, namely WhatsApp. This study aims to determine the role of the use of WhatsApp social media in the distance learning process in Islamic Elementary School (MIN) 4 East Oku. This research is qualitative research. Data collection is conducted by documentation, observation, and interview with 15 students and 3 teachers. The data are analyzed by combining and confirming interview data with observation and documentation data (data triangulation). The results of this study indicate that the use of Whatsapp social media by students in the learning process has been going well because students are familiar with the Whatsapp media application and are easy to access it. The students feel happy and comfortable following the distance learning process which has an impact on learning outcomes that are quite good. However, there are other factors which cause the distance learning process with Whatsapp social media to work well, namely the role of parents who accompany students during the distance learning process.